Thesis in scientific article format by traditional thesis to increase and generate scientific production - Pampa-Quispe, Noe Benjamin (2021)
Currently, Peruvian scientific production is low and therefore there is a concern in universities in how to generate university scientific production. In Peru, scientific production is a priority need in addition to being a requirement of Law 30220 that indicates the obligation to present a research work to obtain the academic degree